Effects of enteral nutritional support on malnourished patients with inflammatory bowel disease by subjective global assessment - Sökülmez, Pınar; Demirbağ, Ali Eba; Arslan, Perihan; Dişibeyaz, Selçuk (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: To investigate the prevalence of malnutrition in patients with inflammatory bowel disease (IBD) by subjective global assessment (SGA) and the effects of oral nutritional support on the clinical parameters, consumption of energy, macronutrients and fiber intake in the Study and Control groups, prospectively. Materials and Methods: A total of 38 (28 Male; 10 Female) hospitalized patients with moderate or severe IBD (13 with Crohn’s disease (CD); 25 with Ulcerative colitis (UC)) were included. At stage 1, the disease severity, clinical symptoms and, signs, food consumption and nutritional status by using subjective global assessment (SGA) were recorded. At stage 2, the patients were blindly randomized into a Study Group and Controls. In the Study Group, a standard enteral product was added into the regulated hospital diets, but for the Controls, deficits were regulated by only hospital diets for 3 weeks. the independent variables were the group, the disease and its activity, age, Body body mass index (BMI), weight loss history, the hospitalization period; the dependent variables were SGA, bowel movements, change in nutritional status, disease severity, clinical findings, and also consumption of macronutrients. Results: Prevalance of malnutrition (SGA-B or SGA-C) for all the patients was 92.1% at the beginning and 71.1% at the end of study. Improvements in disease activity score for the patients with UC were statistically significant in both the Study Group and the Controls (p=0.006 for the Study Group and p=0.001 for the Controls, respectively). Macronutrients, total and water soluble fiber consumption levels improved, with statistically significant differences for all the groups. Conclusion: The prevalence of malnutrition is a major problem in patients with IBD. Not only the regulation of hospital food, but also enteral nutritional support, improved their levels of malnutrition, as well as their energy, macronutrients, and fiber consumption, and SGA is an easy method for nutritional monitoring.